ANALISIS GAYA KEPEMIMPINAN PEREMPUAN DALAM PROSES PENGAMBILAN KEPUTUSAN DI DINAS SOSIAL, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DINSOS P3A) PROVINSI BALI - Ni Putu Arianta Seftiani seftiani; Victorius Adventius Hamel; Anak Agung Gde Brahmantya Murti (Journal of Contemporary Public Administration, 2026)
Women’s leadership in public organizations has gained increasing attention in public administration studies, particularly within bureaucratic contexts that remain dominated by hierarchical authority structures. Although the representation of women in structural positions has increased, changes in organizational decision-making practices have not always occurred significantly. Most previous studies have focused on the characteristics of women’s leadership styles or comparisons with male leadership, leaving limited attention to how women’s leadership is enacted and negotiated within hierarchical bureaucratic structures. This study aims to analyze how women’s leadership is implemented in decision-making processes and how such practices interact with and are negotiated within the bureaucratic power structure at the Department of Social Affairs, Women’s Empowerment, and Child Protection (Dinsos P3A) of Bali Province. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and document analysis involving leaders and staff. Data were analyzed thematically by drawing on the perspectives of collaborative leadership, relational leadership, and postcolonial feminism. The findings indicate that women’s leadership in Dinsos P3A Bali consistently emphasizes collaborative and relational approaches through open communication, participatory discussion forums, and cross-sectoral coordination involving staff in decision-making processes. However, such involvement tends to be consultative in nature, as strategic decisions remain concentrated within the formal authority of top leadership in a hierarchical bureaucratic structure. This condition suggests that women’s leadership does not fundamentally transform bureaucratic power structures but operates adaptively through collaborative strategies within existing institutional constraints. The novelty of this study lies in its analysis of how women’s leadership is negotiated within hierarchical bureaucratic structures, thereby contributing to public administration scholarship, particularly in understanding the dynamics of power relations and the practices of women’s leadership in bureaucratic organizations.